Analisis Tingkat Kesehatan Bank BUMN Menggunakan Metode Risk Profile, Good Corporate Governance, Earning And Capital (RGEC) Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Altaffany Siregar; Elfina O.P. Damanik; Johanes W.P Purba (UNIVED Press, 2022)
Bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit or other forms in order to improve the standard of living of the people at large. The purpose of this research was to analyze the soundness of state-owned banks using the Risk Profile, Good Corporate Governance, Earning, Capital method for the 2016-2020 period. The assessment of the soundness of this bank is based on Bank Indonesia Regulation No. 13/1/PBI/2011 concerning the assessment of the soundness of banks using the RGEC method. This type of research is descriptive quantitative which is a method to explore data or numbers and find knowledge within a certain period of time. The results of the research using the RGEC method at Bank Mandiri, Bank Nasional Indonesia, Bank Tabungan Negara, and Bank Rakyat Indonesia in the 2016-2020 period as a whole reflect the condition of the Bank which is generally